2018
DOI: 10.1007/s13197-018-3298-4
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a broad spectrum bacteriocin produced by a selected Lactococcus lactis strain 63 isolated from Indian dairy products

Abstract: subsp. strain 63 was isolated from Indian dairy products, produced a bacteriocin with broad spectrum inhibition against several of food pathogens like and as well as Gram negative bacteria viz., and strains. Bacteriocin production was higher in GM-17 and MRS as compared to TYGE broth and enriched skim milk broth and reached the maximum level during the early stationary phase. The bacteriocin was purified by performing ammonium sulfate precipitation. The bacteriocin was able to survive 90 °C/10 min but not 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…To evaluate thermal stability, 5 ml aliquots of bacteriocin were subjected to different heat treatments for 80, 90, 100, and 121°C, respectively, for 30 min with treated at room temperature as a control (Zhang et al, 2018). The effect of pH on the antimicrobial activity of the bacteriocin was tested by dissolving the bacteriocin sample of 5 ml of 1 M NaOH or 1 M HCl-adjusted PBS solution at a pH range of 2.0-9.0 (in increments of one pH unit), untreated by acid or alkali as controls (Goyal et al, 2018). To evaluate enzyme stability, it was done by mixing 5 ml of the bacteriocin with pepsin, trypsin, papain, proteinase K, neutral protease, and alkaline proteinase (Sigma) each at 20 mg/ ml concentration to keep the total volume and incubated at 37°C for 30 min (Hong et al, 2014).…”
Section: Sensitivity Of Bacteriocinmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate thermal stability, 5 ml aliquots of bacteriocin were subjected to different heat treatments for 80, 90, 100, and 121°C, respectively, for 30 min with treated at room temperature as a control (Zhang et al, 2018). The effect of pH on the antimicrobial activity of the bacteriocin was tested by dissolving the bacteriocin sample of 5 ml of 1 M NaOH or 1 M HCl-adjusted PBS solution at a pH range of 2.0-9.0 (in increments of one pH unit), untreated by acid or alkali as controls (Goyal et al, 2018). To evaluate enzyme stability, it was done by mixing 5 ml of the bacteriocin with pepsin, trypsin, papain, proteinase K, neutral protease, and alkaline proteinase (Sigma) each at 20 mg/ ml concentration to keep the total volume and incubated at 37°C for 30 min (Hong et al, 2014).…”
Section: Sensitivity Of Bacteriocinmentioning
confidence: 99%
“…Bacteriocin of LAB was a metabolite of lactic acid bacteria which was a kind of bacteriostatic protein synthesized by ribosomes (Wang et al, 2018). It can effectively inhibit the spoilage of food spoilage bacteria and a variety of pathogenic microorganisms (Goyal, Malik, & Pradhan, 2018;Kassaa et al, 2019;Mokoena, 2017), and bacteria were more immune to the produced bacteriocin (Milioni et al, 2015). It can be developed as a new preservative due to its natural nontoxicity and good selectivity (Hwanhlem, Ivanova, Biscola, Choiset, & Haertlé, 2017;Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary tests indicated differences in the inhibitory activity among the isolates [27]; however, these differences were not accounted for by the gene structure. Nisin Z is a bacteriocin potentially active against pathogenic Grampositive bacteria as well as Gram-negative bacteria [33,34]. In addition, De Vos et al [21] reported that His27Asn substitution resulted in a higher diffusion rate of nisin Z, which in turn contributed to the larger inhibition zones produced by nisin Z in agar diffusion assays.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteriocins (BCN) are a group of antimicrobial peptides produced by bacteria when present in intensely competitive niches (Cleveland et al 2001). Considerable research effort has been invested to investigate the use of bacteriocins as a food additive for protection against pathogens (Lewus et al 1991;Scannell et al 2000Scannell et al , 2001Deegan et al 2006;Coelho et al 2007;Xie et al 2009;Zacharof and Lovitt 2012;Goyal et al 2018;Kimura and Yokoyama 2019). As a prophylactic treatment for poultry, significant progress has been made in the development of potent anti-Campylobacter bacteriocins from commensal microbes isolated from the chicken intestinal tract (Lin 2009;Zommiti et al 2016).…”
Section: Bacteriocinsmentioning
confidence: 99%